Service Marketing Strategies in Education: Increasing Competitiveness and Customer Satisfaction - Liana (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Educational institutions increasingly need effective service marketing strategies to strengthen institutional competitiveness and improve customer satisfaction. In the education sector, customers may include students and parents who evaluate schools based on academic programs, tuition value, accessibility, communication, staff service, administrative process, and physical evidence. This study investigated the role of service marketing strategies in increasing institutional competitiveness and customer satisfaction. The study employed a quantitative descriptive-correlational design involving 40 respondents. The variables consisted of service marketing strategies as the independent variable, institutional competitiveness as the first dependent variable, and customer satisfaction as the second dependent variable. Data were collected using a Likert-scale questionnaire converted into a 0-100 score range. The service marketing strategy variable was measured through the 7P dimensions: product, price, place, promotion, people, process, and physical evidence. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings showed that service marketing strategy was categorized as good, with a mean score of 77.65. Institutional competitiveness was also categorized as good, with a mean score of 78.53, while customer satisfaction obtained a good category with a mean score of 79.53. The 7P analysis showed that the highest dimension was people, followed by product and physical evidence, while price received the lowest score. Pearson correlation showed a very strong positive relationship between service marketing strategy and institutional competitiveness, r = .982, p < .001. Service marketing strategy also had a very strong positive relationship with customer satisfaction, r = .991, p < .001. Regression analysis showed that service marketing strategy significantly predicted institutional competitiveness and customer satisfaction. The study concludes that stronger service marketing strategies are associated with higher institutional competitiveness and customer satisfaction in educational services.